PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH, PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DENGAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH KABUPATEN SIJUNJUNG) - Septia Yolanda; Taufeni Taufik; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of effectof regional financial accounting system, regional financial statements presentationand accessibility of regional financial statementson accountability of regional financial management with government internal control system as moderating variable in OPD Sijunjung Regency.The data used in this study is the primary data. The population in this research is all OPD officer of Sijunjung Regency. The sample in this study were 93 people selected by using purposive sampling method. The analysis in this study was conducted using WarpPLS 5.0.The results of this study indicate that the regional financial accounting system and accessibility of regional financial statements affect the accountability of regional financial management while the regional financial statements presentation do not affect the accountability of regional financial management. The government's internal control system moderates the relationship between the regional financial accounting system and the accountability of regional financial management. However, the government's internal control system does not moderate the relationship between regional financial statements presentation and the accessibility of regional financial statements to the accountability of regional financial management.Keywords :Regional Financial Accounting System, Regional Financial Statements Presentation, AccessibilityOf Regional Financial Statements, Accountability Of Regional Financial Management, Government Internal Control System.